Bod XXIII: Indexes to the Bodleian Shelley Manuscripts with addenda, corrigenda, list of watermarks, and related Bodleian - Tokoo, T; Barker-Benfield, B (Routledge, 2002)
Garland's magnificent facsimile series of the manuscripts of Percy Bysshe Shelley and Mary Wollstonecraft Shelley in the Bodleian Library, Oxford (The Bodleian Shelley Manuscripts, 22 volumes, 1986-1997) is now made complete by the publication of its Index-volume. Volume XXIII provides the key to the contents of the Shelleyan notebooks and papers in all their complexity: poems, prose, translations, fragments, calculations, drawing and doodles, addresses and other miscellaneous jottings. The accumulated findings provide a treasure-trove of information about the Shelley's lives: their writings and readings, and echoes of classical and later authors; the people they met, corresponded with, rented houses from, or saw perform; the towns they visited, the very houses in which they lived, the lakes and rivers they sailed and the mountains they climbed. The intellectual and physical data of these manuscripts will help open new vistas for students of their lives, thought and creative writing.